2022
DOI: 10.3390/ma15238314
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Processing of Fine Dusts from the Electric Smelting of Ilmenite Concentrates to Obtain Titanium Dioxide

Abstract: This article presents studies on the ammonium fluoride processing of dusts from the reduction smelting of ilmenite concentrate with separation of silicon to obtain titanium dioxide. Optimal conditions for pyrohydrolysis of titanium fluorides were determined. The effects of temperature and duration on the process were studied. The optimal conditions for pyrohydrolysis of titanium fluorides were a temperature of 600 °C and duration of 240–300 min. The degree of titanium fluoride conversion to titanium oxide was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…High quality of pigmental titanium dioxide is provided by the rutile phase; therefore, titanium dioxide was calcined at a temperature of 900 • C for 2 h to obtain the rutile modification. The TiO 2 content was 99.8 wt%, and the content of impurities of silicon, chromium, manganese, and iron in recalculation on their oxides was 0.0005, 0.032, 0.005, and 0.039 wt%, respectively, in the obtained rutile product [36]. According to the content of the main component and accompanying impurities, the product complies with the requirements of the state standard GOST 9808-84 for pigment titanium dioxide [37].…”
Section: Titanium Dioxide Production and Purificationmentioning
confidence: 94%
See 2 more Smart Citations
“…High quality of pigmental titanium dioxide is provided by the rutile phase; therefore, titanium dioxide was calcined at a temperature of 900 • C for 2 h to obtain the rutile modification. The TiO 2 content was 99.8 wt%, and the content of impurities of silicon, chromium, manganese, and iron in recalculation on their oxides was 0.0005, 0.032, 0.005, and 0.039 wt%, respectively, in the obtained rutile product [36]. According to the content of the main component and accompanying impurities, the product complies with the requirements of the state standard GOST 9808-84 for pigment titanium dioxide [37].…”
Section: Titanium Dioxide Production and Purificationmentioning
confidence: 94%
“…Obtained fluoride sublimations of titanium have the following composition (wt%): 59.0 Ti; 0.6 Fe; 0.005 Si; 0.09 Cr; 0.14 Al; 20.4 F; and 19.8 O. Studies of titanium fluoride pyrohydrolysis with the investigation of the influence of temperature (in the range from 300 to 700 • C) and duration of the process (in the range from 1 to 5 h) have shown that optimal parameters are 600 • C and a duration of 4-5 h [36].…”
Section: Titanium Dioxide Production and Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The high rates of development of these technology branches determine the continuous increase in demand for rare metals which provides for further expansion of their production [ [1], [2], [3]]. The use of titanium-magnesium production waste abundant in rare metals can contribute to solving this problem [4]. Niobium and zirconium are a common satellite of titanium; therefore, they are found in titanium concentrates obtained from ores of ilmenite deposits.…”
Section: Introductionmentioning
confidence: 99%
“…They also proposed an experimental study on ultrasound-enhanced sulfuric acid leaching for zinc extraction from zinc oxide dust [5]. Ultarakova et al present studies on the ammonium fluoride processing of dust from the reduction smelting of ilmenite concentrate with silicon separation to obtain titanium dioxide [6]. Optimal conditions for pyrohydrolysis of titanium fluorides were determined.…”
mentioning
confidence: 99%